Criminal Law Characteristics of Criminal Offences Under Article 190 of the Criminal Code of Ukraine - S. O. Serbenyuk (Bulletin of Kharkiv National University of Internal Affairs, 2025)
Fraud exists in a wide range of social relations, including domestic, economic and other relations. At the same time, the development of technology and the emergence of new areas of economic relations (for example, virtual assets (cryptocurrencies) and cashless payments) contribute to the emergence of new techniques for committing fraud, while a low level of legal culture and selfish motives are the driving force behind the spread of fraudulent activities in social relations. The problem of preventing and combating fraud is particularly relevant in conditions of economic crisis or high inflation, martial law or a state of emergency, etc. In recent years, the number of such criminal offences has been on the rise.